Análise de resistência a flexão de compósitos poliméricos com fibras de bambu e resíduo de cobre - SANTOS, Fagner Sales dos (2022)
The search for sustainability, reuse and low cost is part of the materials engineering research area, in addition to minimizing ecological damage using biodegradable materials, we also aim to reduce waste of material in the environment, re-using materials such as copper. In this study, we gathered this search, with a bending (Flexion) mechanical testing of a association polymer with copper waste (CUW), short (15 mm) bamboo fibers (BF) treated (TR) and untreated (NT), in composites of polymeric matrix (PM), made according to the ASTM D790 standard, using the measures of 3.0x127x12.5 mm.